Serotonin Syndrome Presenting as a Posterior Reversible Encephalopathy Syndrome - Malik, Muhammad Taimur; Majeed, Mohammad Faraz; Zand, Ramin (Case reports in neurology, 2020)
Posterior reversible encephalopathy syndrome (PRES) is a neurological syndrome characterized by an altered level of consciousness, headaches, seizure, and visual changes. PRES has several different etiologies, including malignant hypertension, eclampsia, and certain medications. Here, we describe a 41-year-old woman who presented with altered mental status. She had a preliminary diagnosis of serotonin syndrome as she was on many different serotonin-sparing agents, but her imaging findings were consistent with PRES. After her medications were reviewed and the causative agent was removed, the patient’s neurological exam and imaging findings improved, and she returned to her baseline. To our knowledge, this is a unique case of PRES caused by serotonin syndrome secondary to venlafaxine usage.